About «Factors determining irregular attendance to follow-up visits among human immunodeficiency virus patients: Results of a hospital survey of patients infected with human immunodeficiency virus, 2002-2012» - Guillermo Ladera, Dayana Sianny (2016)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.